A Structured Process Description of a Pragmatic Implementation Project: Improving Integrated Care for Older Persons in Residential Care Homes. (21st November 2017) - Poot, Antonius J.; de Waard, Claudia S.; Wind, Annet W.; Caljouw, Monique A. A.; Gussekloo, Jacobijn
Evaluation of the implementation of integrated care can differ from trial-based research due to complexity. Therefore, we examined whether a theory-based method for process description of implementation can contribute to improvement of evidence-based care. MOVIT, a Dutch project aimed at implementing integrated care for older vulnerable persons in residential care homes, was used as a case study. The project activities were defined according to implementation taxonomy and mapped in a matrix of theoretical levels and domains. Project activities mainly targeted professionals (both individual and group). A few activities targeted the organizational level, whereas none targeted the policy level, or the patient, or the "social, political, and legal" domains. However, the resulting changes in care delivery arrangement had consequences for professionals, patients, organizations, and the social, political, and legal domains. A structured process description of a pragmatic implementation project can help assess the fidelity and quality of the implementation, and identify relevant contextual factors for immediate adaptation and future research. The description showed that, in the MOVIT project, there was a discrepancy between the levels and domains targeted by the implementation activities and those influenced by the resulting changes in delivery arrangement. This could have influenced, in particular, the adoption and sustainability of the project.